HUBUNGAN PENERAPAN PENDEKATAN SAINTIFIK, MINAT, DAN KEMAMPUAN MENULIS SISWA SMA KRISTEN IMMANUEL PONTIANAK - Serapina, Serapina; Sulissusiawan, Ahadi; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This thesis is entitled "The Relationship between Application of Scientific Approach, Writing Interests, and Writing Ability of High School Christian Immanuel Pontianak Student Report". This study aims to determine the relationship between the application of scientific approach, interest in writing, and writing skills of Christian Immanuel Pontianak High School students. The research method used is descriptive method with correlation research form. The data source of this research is the students of SMA Kristen Immanuel Pontianak class X. Technique of collecting data using written test and indirect communication that is written test conducted by executing report writing activity, whereas communication is not done directly by using questionnaire or questionnaire. The data were analyzed using product moment statistic calculation, with the result of research relation of the application of scientific approach with writing ability of report 0,226 hence there is positive relation, the correlation between interest of writing with writing ability report 0,148 hence there is positive relation, relation between applying of scientific approach, and writing ability has a significant relationship that is equal to 3,49> 3,26.Keywords: Scientific Approach, Interests, Writing Ability